Evaluation Study on Rural Telephony States Specific Reports (Volume - II), Programme Evaluation Organisation Planning Commission, Government of India - Planning Commission (Planning Commission, 2010)
Andhra Pradesh lies between 12°41' and 22° longitude and 77° and 84°40' latitude. Madhya Pradesh and Orissa in the north, the Bay of Bengal in the east, Tamil Nadu and Karnataka in the south and Maharashtra in the west, bound Andhra Pradesh. Andhra Pradesh is the fifth largest state in India. It is the biggest and most populous state in the south of India. There are three main regions in Andhra Pradesh - (1) Northern Circars or coastal Andhra comprising Srikakulam, Visakhapatnam, East Godavari, West Godavari, Krishna, Guntur, Ongole and Nellore districts; (2) Rayalaseema or Ceded districts comprising Kumool, Cuddapah, Chittoor and Anantapur districts; and (3) Telangana comprising Khammam, Nalgonda, Warangal, Karimnagar, Medak, Nizamabad, Adilabad, Mahbubnagar, Ranga Reddy and Hyderabad districts. The Circars or Coastal districts are well developed and enjoy a greater degree of affluence than the other two regions; Rayalaseema is close to the coastal districts and here rainfall is less than in the coastal districts and drought conditions prevail sometimes, and the Telangana region is of the former princely state of Nizam's Hyderabad, which is close to Maharashtra's Marathwada region and some parts of Karnataka.
Evaluation Study on Rural Telephony States Specific Reports (Volume - II)
Government of India